Application of enhanced recovery after surgery in partial nephrectomy for renal tumors: A systematic review and meta-analysis - Wangjian, Wu; Tianyi, Lu; Xiaoqian, Ma; Di, Zhang; Chuan, Zhou; Chao, Wang; Zijian, Da; Tongtong, Jin; Fenghai, Zhou (Frontiers in Oncology, 2023)
Objectives In recent years, enhanced recovery after surgery (ERAS) has been widely used in the field of urology, especially in radical cystectomy and radical prostatectomy, and has demonstrated its advantages. Although studies on the application of ERAS in partial nephrectomy for renal tumors are increasing, the conclusions are mixed, especially in terms of postoperative complications, etc, and its safety and efficacy are questionable. We conducted a systematic review and meta-analysis to assess the safety and efficacy of ERAS in the application of partial nephrectomy for renal tumors. Methods Pubmed, Embase, Cohrance library, Web of science and Chinese databases (CNKI, VIP, Wangfang and CBM) were systematically searched for all published literature related to the application of enhanced recovery after surgery in partial nephrectomy for renal tumors from the date of establishment to July 15, 2022, and the literature was screened by inclusion/exclusion criteria. The quality of the literature was evaluated for each of the included literature. This Meta-analysis was registered on PROSPERO (CRD42022351038) and data were processed using Review Manager 5.4 and Stata 16.0SE. The results were presented and analyzed by weighted mean difference (WMD), Standard Mean Difference (SMD) and risk ratio (RR) at their 95% confidence interval (CI). Finally, the limitations of this study are analyzed in order to provide a more objective view of the results of this study. Results This meta-analysis included 35 literature, including 19 retrospective cohort studies and 16 randomized controlled studies with a total of 3171 patients. The ERAS group was found to exhibit advantages in the following outcome indicators: postoperative hospital stay (WMD=-2.88, 95% CI: -3.71 to -2.05, p<0.001), total hospital stay (WMD=-3.35, 95% CI: -3.73 to -2.97, p<0.001), time to first postoperative bed activity (SMD=-3.80, 95% CI: -4.61 to -2.98, p < 0.001), time to first postoperative anal exhaust (SMD=-1.55, 95% CI: -1.92 to -1.18, p < 0.001), time to first postoperative bowel movement (SMD=-1.52, 95% CI: -2.08 to -0.96, p < 0.001), time to first postoperative food intake (SMD=-3.65, 95% CI: -4.59 to -2.71, p<0.001), time to catheter removal (SMD=-3.69, 95% CI: -4.61 to -2.77, p<0.001), time to drainage tube removal (SMD=-2.77, 95% CI: -3.41 to -2.13, p<0.001), total postoperative complication incidence (RR=0.41, 95% CI: 0.35 to 0.49, p<0.001), postoperative hemorrhage incidence (RR=0.41, 95% CI: 0.26 to 0.66, p<0.001), postoperative urinary leakage incidence (RR=0.27, 95% CI: 0.11 to 0.65, p=0.004), deep vein thrombosis incidence (RR=0.14, 95% CI: 0.06 to 0.36, p<0.001), and hospitalization costs (WMD=-0.82, 95% CI: -1.20 to -0.43, p<0.001). Conclusion ERAS is safe and effective in partial nephrectomy of renal tumors. In addition, ERAS can improve the turnover rate of hospital beds, reduce medical costs and improve the utilization rate of medical resources. Systematic review registration https://www.crd.york.ac.uk/PROSPERO, identifier CRD42022351038.